Mechanisms and consequences of life cycle diversity of beaked redfish, Sebastes mentella - Cadrin, Steven X.; Bernreuther, Matthias; Daníelsdóttir, Anna Kristín; Hjörleifsson, Einar; Johansen, Torild; Kerr, Lisa; Kristinsson, Kristjan; Mariani, Stefano; Pampoulie, Christophe; Reinert, Jákup; Saborido-Rey, Fran; Sigurdsson, Thorsteinn; et al. (ICES, 2009)
Recent genetic research, supported by life history information, indicates that there are three biological stocks of S. mentella in the Irminger Sea and adjacent waters: a ‘Deep Pelagic’ stock (>500m), a ‘Shallow Pelagic’ stock (<500m), and an ‘Icelandic Slope’ stock. Throughout their range, Sebastes species are adapted to a diversity of ecological niches, with overlapping spatial distributions of different species that have little or no morphological differences. Divergence of behavioral groups into depth-defined adult habitats has led to reproductive isolation, adaptive radiation and speciation of several Sebastes species. Congruent differences in fatty acid composition and parasites suggests that the three genetically distinct populations of S. mentella are adapted to disparate trophic habitats in pelagic waters (shallower and deeper than the deep-scattering layer), and in demersal habitats on the continental slope. Patterns of morphology are also consistent with adaptation to different habitats, because pelagic forms are more streamlined. Although genetic differences and evidence for reproductive isolation are clear, these populations appear to share common nursery habitats on the Greenlandic Shelf. Spatial overlap at early life stages and depth-defined adult populations present challenges for stock identification and fishery management. Effective resource monitoring, conservation and fishery management requires that the spatial definition of management units reflects biological stock structure. We describe a proposal for a redefinition of practical management units that are based on geographic proxies for biological stocks which minimizes mixed-stock catches according to spatial patterns of the recent fishery.